Elastic and inelastic scattering of 14N ions by 7Li at 80 MeV - A. T. Rudchik; O. V. Gerashchenko; A. A. Rudchik; E. I. Koshchy; S. Kliczewski; K. Rusek; S. Yu. Mezhevych; V. A. Plujko; O. A. Ponkratenko; Val. M. Pirnak; A. P. Ilyin; V. V. Uleshchenko; et al. (Ядерна фізика та енергетика)
Angular distributions of the 7Li + 14N elastic and inelastic scattering as well as the 7Li(14N, Х) reactions with production of 13, 15, 16N + 8, 6, 5Li, 11, 12, 13, 14С + 10, 9, 8, 7Ве, 10, 11, 12В + 11, 10, 9В nuclei and others were measured at Elab (14N) = 80 MeV. The data were analyzed within the optical model and coupled-reaction-channels method. The elastic and inelastic scattering, reorientations of 7Li and 14N in ground and excited states as well as the prominent one- and two-step transfers were included in a channels-coupling-scheme. The 7Li + 14N optical potential parameters for ground and excited states of 7Li and 14N as well as deformation parameters of these nuclei were deduced. The contributions of one and two-step transfers in the 7Li + 14N elastic and inelastic scattering channels were estimated.